Early development of the optic chiasm in the gray short-tailed opossum, Monodelphis domestica. - Taylor, J; Guillery, R (1994)
We have studied the early development of the uncrossed retinofugal projection in the gray short-tailed opossum. Axons that form the adult uncrossed retinofugal projection arise from the temporal crescent of the retina and reach the optic chiasm on postnatal day 7. The sites at which the uncrossed fibres segregate from the crossed fibres and the pattern of this segregation are very different from those seen in eutherian mammals. In the opossum, the uncrossed fibres segregate from the crossed fibres within the juxtachiasmatic part of the optic nerve before they have encountered either the fibres of the other eye or midline structures of the ventral diencephalon. The uncrossed fibres turn perpendicular to the axis of the nerve and grow dorsoventrally through the crossed projection to gather as a discrete bundle at the ventral edge of the nerve. The abrupt divergence of the uncrossed fibres occurs at a border between two glial cell types: the interfascicular glia that characterise the main part of the optic nerve and the radial glia of the juxtachiasmatic part of the nerve. At the ventral part of the nerve, the bundle of uncrossed fibres turns caudally across the axis of the nerve and enters the ipsilateral optic tract. When retinofugal fibres encounter the border between the interfascicular and radial glia, a very specific axonal reorganisation occurs in marsupials, and this is strikingly different from the axonal reorganisation that occurs at the same site in eutherians, where essentially all retinofugal fibres reorganise, not just the uncrossed component. We believe this to be an important example of an identified cellular element that has quite distinct axon-guidance properties in different species.